On the Link between the Protection of Minorities' Intangible Cultural Heritage and the Evaluation of Social Sciences and Humanities in the Republic of Serbia: Preliminary Examination of Cross-Study Results - Miloš Milenković (University of Belgrade, 2021)
The results of theoretical and field research into a) the state of protection of minorities' intangible cultural heritage, and b) the evaluation criteria for social sciences and humanities in the Republic of Serbia, indicate a clear and concerning correlation. Seemingly paradoxically, social sciences and humanities in the Serbian language are in an equally unfavorable, undervalued position as is the cultural heritage of minorities relative to that of the majority population's. Analysis suggests that, although they mostly do not perceive themselves in this way, Serbian social sciences and humanities scholars are a vulnerable social group in the sector of science and higher education, in the same sense in which ethnic minorities and communities are in terms of government cultural policy. The paper, based on the conclusions of an analysis of selected cross-study findings of field and theoretical research over a number of years, also proposes how the existing vulnerability factors can be eliminated and future ones prevented, particularly through cooperation between these two, often mutually opposed groups.